Bifurcation for Some Systems of Cooperative and Predator-prey Type (Journal of Partial Differential Equations, 1992)
In this paper we provide a full classification of the non-negative solutions types for a class or two-dimensional bilinear cooperative aud predator-prey systems in terms of two bifurcation parameters.